SAMPLE PREPARATION AND HPLC ANALYSIS OF METFORMIN IN PLASMA OF WOMEN WITH POLYCYSTIC OVARY SINDROME - Sunarić, Slavica; Denić, Marko; Trajković, Hristina; Nikolić, Valentina; Stefanović, Milan; Živanović, Snežana; Živanović, Sonja (Archives of Pharmacy, 2021)
In recent years, polycystic ovary syndrome (PCOS) is a common endocrinopathy that affects approximately 5% to 10% of women at reproductive age (1). Metformin (MTF) or dimethyl biguanide is oral antidiabetic drug which is also being used in the treatment of PCOS, but its therapeutic regiments for this purpose are still not well standardized (2). Sample preparation is important step in bioanalysis and the extraction of MTF from biological samples is somewhat complicated by the polar nature of this molecule. The aims of this study were optimizing sample preparation procedure, as well as, evaluation and validation of HPLC method for determination of metformin in plasma obtained from women with PCOS. Blood plasma samples were collected from women with PCOS (n=54), 2-3h after the dosing. Extractions with different polar organic solvents and water solutions of acids (methanol, ethanol, acetonitrile, 10% HClO4, 10% trichloroacetic acid) were performed, followed by centrifugation and filtration through 0.45 μm membrane filter. Twenty microliters of supernatant was injected on Zorbax-NH2 column and the separation of MTF was achieved at 30 °C using isocratic elution. The mobile phase was consisted of 100% acetonitrile with flow rate 0,725 mL/min. The detection was monitored at 232 nm and quantification was done by calibration curve method. After optimization of experimental conditions, the highest values for recovery (over 92%) for MTF from blank plasma samples spiked with standard were obtained by preparation with small volume of acetonitrile. For optimized HPLC analysis, good linearity was found in the range of 0.1-5.0 μg/mL (r=0.9997), detection and quantification limits were 0.053 μg/mL and 0.175 μg/mL. Applying the chosen sample preparation procedure and HPLC analysis, the obtained concentrations of MTF in plasma of women with PCOS were in the range 1,24±0,07 μg/mL to 2,38±0,17 μg/mL, whereas precision was also satisfying (RSD<8.5%). The proposed method analysis was based on simple procedure by using one organic solvent and small volume of collected biological sample, as well as on the use of simple mobile phase and polar amino column. This combination of selected chromatographic conditions enabled very short retention time of MTF (around 3.7 min) and total time of one chromatographic run less than 6 min. Furthermore, satisfactory analytical parameters in terms of validation for the analysis of MTF in plasma of women with PCOS were obtained.